Phenotypic prevalence of obesity and metabolic syndrome among an underdiagnosed and underscreened population of over 50 million children and adults - Kim, Eric GR; Kaelber, David C (Frontiers in Genetics, 2022)
Metabolic syndrome is a phenotypic condition associated with a variety of genotypes. Studies of rare genotypes can be made more difficult by clinical underscreening of the population for the phenotypic traits that define metabolic syndrome to clinicians. Studies have demonstrated underdiagnosis of pediatric obesity, as well as reduced rates of pediatric screening for obesity related conditions, including conditions leading to a diagnosis metabolic syndrome. If true, there may be a significant underdiagnosis of metabolic syndrome among the pediatric population compared to the adult population. Using Epic’s Cosmos Data Network aggregated, de-identified patient data collected from healthcare organizations using the Epic electronic health record (EHR), we examined obesity and metabolic syndrome rates among adult and pediatric patients. We also examined screening rates for obesity related conditions and metabolic syndrome among adult and pediatric patients across the US. We also sought to compare rates between subgroups within the sample including age, sex, and race. In our sample, 45% of adults and 27% of pediatric population were obese by age and gender specific BMI criteria. 38% of the obese adult had an ICD-10 code associated with the diagnosis vs 52% of the pediatric sample. Of obese adults, 36% had results for appropriate, guideline-based workup of insulin resistance, 40-42% for dyslipidemia, and 55% for hepatic steatosis. 36% of obese adult patients had no lab workup. 31% of the adult population met diagnostic criteria for metabolic syndrome. Of obese pediatric patients, 27% had results for appropriate workup of insulin resistance, 28% for dyslipidemia, and 33% for hepatic steatosis. 59% of obese pediatric patients had no lab workup. 3% of the pediatric population met criteria for diagnosis of metabolic syndrome. Although obesity is better diagnosed in pediatric vs adult patients, significantly lower screening rates for obesity related conditions occurred in pediatric patients vs adults. Additionally, differences in screening rates were found by race and gender, though these differences were relatively small. These results support smaller prior studies that suggest that obesity is under-diagnosed and obesity related conditions underscreened in the pediatric population, and additionally suggests underdiagnosis of metabolic syndrome among US pediatric and adult patients.